Effectiveness of Health Educational Program on Mother‘s Home Care Management toward Their Children with Cerebral Palsy at Medical Rehabilitation Center in Baghdad City. - Shared, Zahraa Y.; Hatab, Khatam M. (International Journal of Psychosocial Rehabilitation, 2020)
Objectives:- The present study ought to assess mothers home care for child with CP Methodology :- The study design is a quasi-experimental, the study was carried out to evaluate the Effectiveness of an Education Health Program on Mother‘s Home Care Management toward Their Children with Cerebral Palsy at Medical Rehabilitation Center in Baghdad City between January 27th, 2020 to feberuray 27th 2020 .The research sample includes (20) mothers of children with cerebral palsy, they are selected by using non probability sampling (purposive sample) from the Medical Rehabilitation Center. Results:- The program has effectiveness on the maternal home care for their children with cerebral palsy during the 2 period of test, the sample have low level of assessment before implementation of an education health program and the level of assessment ascend to high level after implementation of an education health program. Recommendations:- Implementation of the education health program to improve the mothers home care for their children with cerebral palsy. Training session for the mothers about how to carry the child, daily activity, baby need of nutrition, playing communication, and assistant device that help the child and how to use it.